Evaluating the impact of a maternal health voucher programme on service use before and after the introduction of free maternity services in Kenya: a quasi-experimental study. Issue 2 (2nd May 2018) - Dennis, Mardieh L; Abuya, Timothy; Campbell, Oona Maeve Renee; Benova, Lenka; Baschieri, Angela; Quartagno, Matteo; Bellows, Benjamin
Abstract : Introduction: From 2006 to 2016, the Government of Kenya implemented a reproductive health voucher programme in select counties, providing poor women subsidised access to public and private sector care. In June 2013, the government introduced a policy calling for free maternity services to be provided in all public facilities. The concurrent implementation of these interventions presents an opportunity to provide new insights into how users adapt to a changing health financing and service provision landscape. Methods: We used data from three cross-sectional surveys to assess changes over time in use of 4+ antenatal care visits, facility delivery, postnatal care and maternal healthcare across the continuum among a sample of predominantly poor women in six counties. We conducted a difference-in-differences analysis to estimate the impact of the voucher programme on these outcomes, and whether programme impact changed after free maternity services were introduced. Results: Between the preintervention/roll-out phase and full implementation, the voucher programme was associated with a 5.5% greater absolute increase in use of facility delivery and substantial increases in use of the private sector for all services. After free maternity services were introduced, the voucher programme was associated with a 5.7% higher absolute increase in use of the recommended package of maternal health services; however, disparities in access to facility births between voucher and comparison counties declined. Increased use of private sector services by women in voucher counties accounts for their greater access to care across the continuum. Conclusions: Our findings show that the voucher programme is associated with a modest increase in women's use of the full continuum of maternal health services at the recommended timings after free maternity services were introduced. The greater use of private sector services in voucher counties also suggests that there is need to expand women's access to acceptable and affordable providers.